Application on the impact domain analysis of on-orbit maintenance in China Space Station. Issue 3 (January 2021) - Lv, Zhen; Zhang, Hua; Zhao, Zhi-Ming; Gong, Kai-Xiang
Abstract: On-orbit maintenance is an important means to extend the service life and improve the reliability of the space station. As an essential part of maintainability analysis, impact domain analysis of on-orbit maintenance can find out the deficiency of maintainability design in advance and reduce the risk brought by maintenance. In this paper, the analysis method of the impact domain of the space station on-orbit maintenance is studied, and the working idea of "stage by stage, full coverage, focusing on key points" is put forward to adapt to the development and needs of China Space Station. The process, object, content, and analysis emphasis of the impact domain analysis for different development phases and different kinds of products are determined. The engineering practice shows that reasonable maintenance process and optimal design can be determined by the analysis of the impact area of on-orbit maintenance, which lays the foundation for the good maintainability of China Space Station.